Atomistic evidence of hydrodynamic heat transfer in nanowires. (15th September 2022) - Desmarchelier, Paul; Beardo, Albert; Alvarez, F. Xavier; Tanguy, Anne; Termentzidis, Konstantinos
Highlights: The radial heat flux distribution in silicon nanowires has a Poiseuille-like shape. The addition of an amorphous shell decrease the heat flux in the center. The heat flux at the interface is not affected by the presence of a shell. The radial distribution can be fitted using the hydrodynamic heat equation. The effect of the shell is modeled by changing the thermal conductivity. Abstract: With wave-packet propagation simulations and heat flux estimation via molecular dynamics, we show that the heat flux radial distribution in silicon nanowires can be described by a mesoscopic model, the hydrodynamic heat equation. We observe Poiseuille like heat flux profile, that cannot be described by a simple kinetic model such as the Fuchs-Sondheimer model, in both pristine and core/shell nanowires. The addition of a shell does not change the shape of the radial heat flux distribution, but just modifies the maximum of the heat flux in the center of the nanowire. These results show that there is a heat flux depletion length for pristine or core shell nanowires, 1–2 nm away from the boundary of the crystalline part. The parameters of the mesoscopic model are discussed in terms of microscopic properties, including the phonon mean free path as function of frequency and the partial vibrational density of states in the different regions of the nanowire.